Wayang Kancil Story Telling to Improve The Tolerance of Elementary School Students - Winarsih, Tri; Komarudin, Komarudin (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2020)
The tolerance attitude of Indonesian people today are beginning to fade, along with the increasing cases of intolerance in our society, including in the education field. Issues such as abuse, fights, and bullying are examples of intolerant attitudes that are increasing nowadays. Education at the elementary school level is the foundation for the formation of children's character so that at this level, knowledge is essential to teach tolerance. One method that is proven effective for instilling character education is storytelling using Wayang Kancil. So, this method needs to test for its effectiveness in establishing a tolerance for elementary students. The purpose of this study is to find out whether storytelling using Wayang Kancil can improve tolerance for elementary students. This study used a quasi-experimental method, which involved two elementary schools as an experimental group and a control group. The storyteller gives the stimulus of storytelling using Wayang Kancil. Tolerance measurements in subjects were carried out both before and after the administration of treatment. Measurements are made by providing a scale of tolerance. This study using a non-parametric statistical analysis Mann-Whitney U Test. This test is to find out whether there are differences in patience in the experimental group and the control group, namely pretest, and posttest. The results showed significant differences between tolerance in the experimental group and the control group (p = 0.008, α <0.05). Tolerance attitude in the experimental group after being given the storytelling, the results were higher than the control group Sikap toleransi pada Bangsa Indonesia dewasa ini mulai memudar, seiring meningkatnya kasus-kasus intoleransi di tengah-tengah masyarakat, termasuk pada dunia pendidikan. Kasus-kasus seperti perundungan, perkelahian, dan tawuran pelajar merupakan contoh sikap intoleran yang semakin marak terjadi. Pendidikan pada jenjang Sekolah Dasar (SD) merupakan pondasi pembentukan karakter anak, sehingga pada jenjang ini sangat perlu diberikan pendidikan mengenai toleransi. Salah satu metode yang terbukti efektif untuk menanamkan pendidikan karakter adalah dongeng menggunakan Wayang Kancil. Untuk itu, metode ini pun perlu diuji efektivitasnya dalam menamamkan sikap toleransi pada siswa SD. Tujuan dari penelitian ini yaitu untuk mengetahui apakah dongeng dengan media Wayang Kancil mampu meningkatkan sikap toleransi pada siswa SD. Penelitian ini menggunakan metode quasi eksperimen, yang melibatkan dua kelas dari dua SD sebagai kelompok eksperimen dan kelompok kontrol. Stimulus berupa dongeng menggunakan media Wayang Kancil diberikan oleh pendongeng. Pengukuran toleransi pada subjek dilakukan baik sebelum dan sesudah pemberian perlakuan. Pengukuran dilakukan dengan memberikan skala sikap toleransi. Pengujian terhadap hipotesis penelitian ini menggunakan analisis statistik non parametrik Mann-Whitney U Test. Pengujian ini untuk mengetahui apakah ada perbedaan sikap toleransi pada kelompok eksperimen dan kelompok kontrol, yaitu pretest, dan posttest. Hasil penelitian menunjukkan bahwa terdapat perbedaan yang signifikan antara sikap toleransi pada kelompok eksperimen dan kelompok kontrol (p=0,008, ?<0,05). Sikap toleransi pada kelompok eksperimen setelah diberikan dongeng, hasilnya lebih tinggi dibanding kelompok kontrol.